Como um pai deve ser (e não ser) : paternidade nos discursos de jovens pais da Baixada Cuiabana - Pereira Neto, Ataíde Martins (2021)
In this work, we propose to debate “new forms of fatherhood”. For this purpose, we submitted young fathers from the Cuiabá city region to a field study and a questionnaire, which created the title of this research, How a father should be (and not be): Fatherhood in the Discourses of Young Fathers of the city. In this project, seven parents voluntarily expose their actions, practices and opinions about paternity, marriage, children, home, domestic work, public etc. The research consists of two groups of parents, the first comes from my social life, they are young parents who live in the same neighborhood, on the outskirts of Várzea Grande - MT, belonging to the lower middle class, the second is parents who live in closed condominiums in the city of Cuiabá - MT, they are not part of my social life, they declare themselves as belonging to the middle class. During this research, the observations, the writings that submit these parents, to a methodological analysis, are not limited to class issues, even though these directly influence the rhetoric of these parents. Our object is linked to the observation about the continuities and changes in relation to the forms of paternity. The proposal starts from the analysis of the family arrangements to which these parents belong, understanding, from the perspective projected from their own paternal reference point and from the confrontation with reports from other young parents, the relationship they establish with domestic spaces, children and familiar settings in general. Much more than categorizing a possible classification of "new man" or "new father", our proposal moves from identity studies to focus on the rhetoric of practices and behaviors within power relations at the center of family arrangements and spaces domestic and/or public to which it belongs.